Taste Quality Confusions: Influences of Age, Smoking, PTC Taster Status, and other Subject Characteristics. (March 2017) - Doty, Richard L.; Chen, Jonathan H.; Overend, Jane
Many persons misidentify the quality of taste stimuli, a phenomenon termed "taste confusion." In this study of 1000 persons, we examined the influences of age, sex, causes of chemosensory disturbances, and genetically determined phenylthiocarbamide (PTC) taster status on taste quality confusions for four tastants (sucrose, citric acid, sodium chloride, caffeine). Overall, sour-bitter confusions were most common (19.3%), followed by bitter-sour (11.4%), salty-bitter (7.3%), salty-sour (7.0%), bitter-salty (3.5%), bitter-sweet (3.4), and sour-salty (2.4%) confusions. Confusions for sweet were <1%. Asymmetries were common (e.g., bitter-sour confusions were less frequent than sour-bitter confusions). Women had fewer salty-bitter confusions than did men (5.7% vs. 11.4%). Overall, PTC tasters had fewer confusions than non-tasters except for salty-bitter confusions. Confusions typically increased monotonically with age. Current smokers exhibited more sour-bitter confusions than never smokers (48.9% vs. 32.2%), whereas past smokers had more bitter-sour confusions than never smokers (23.8% vs. 14.2%). Previous head trauma was associated with higher bitter-salty and salty-bitter confusions relative to those of some other etiologies. This study demonstrates, for the first time, that multiple subject factors influence taste confusions and, along with literature accounts, supports the view that there are both biological and psychological determinants of taste quality confusions.